2008
DOI: 10.1007/s10856-008-3590-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid biofabrication of tubular tissue constructs by centrifugal casting in a decellularized natural scaffold with laser-machined micropores

Abstract: Centrifugal casting allows rapid biofabrication of tubular tissue constructs by suspending living cells in an in situ cross-linkable hydrogel. We hypothesize that introduction of laser-machined micropores into a decellularized natural scaffold will facilitate cell seeding by centrifugal casting and increase hydrogel retention, without compromising the biomechanical properties of the scaffold. Micropores with diameters of 50, 100, and 200 mum were machined at different linear densities in decellularized small i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…If this goal can be achieved the probability of translating the technology to clinical application will be significantly improved. Attempts have been made to overcome this problem within synthetic scaffolds for vascular applications using rotational vacuum techniques (Soletti et al, 2006, Nieponice et al, 2008, Kasyanov et al, 2009, Godbey et al, 2004, the high porosity and large pore size make these scaffolds easier to seed with large cell numbers in short time periods. While in the case of dense decellularized tissue bulk seeding the medial layer has not been successfully achieved.…”
Section: Discussionmentioning
confidence: 99%
“…If this goal can be achieved the probability of translating the technology to clinical application will be significantly improved. Attempts have been made to overcome this problem within synthetic scaffolds for vascular applications using rotational vacuum techniques (Soletti et al, 2006, Nieponice et al, 2008, Kasyanov et al, 2009, Godbey et al, 2004, the high porosity and large pore size make these scaffolds easier to seed with large cell numbers in short time periods. While in the case of dense decellularized tissue bulk seeding the medial layer has not been successfully achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Once a tubular structure can be built, most other biological structures are attainable, as they are comprised of a combination of tubular or hollow structures and simpler cell arrangements. 14,15 A major hurdle has been that few biomaterials have been developed with design criteria specific to bioprinting.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26] The ease with which 3D tissue culture can be performed in vitro and in vivo has made this biomaterial appropriate for new tissue engineering research applications such as development of bladder tissues, centrifugally cast vessel-like tubes, and tumor xenograft models for drug and discovery. 14,18,[27][28][29][30][31][32] Despite these many applications, however, the polyethylene glycol diacrylate (PEGDA)-crosslinked thiolated HA-based sECMs were found to be unsuitable for bioprinting. Because they could not maintain structural integrity during printing and would frequently clog the print heads, a new crosslinking chemistry was needed.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the effective reendothelization of a complete intra-organ vascular system remains to be demonstrated. It has however been demonstrated that introduction of laser-machined micropores helps to improve recellularization of natural-scaffold-derived vascular grafts and enhances its vascularization after implantation [17]. How this technology can be adapted to thick 3D decellularized whole organ scaffolds remains to be seen.…”
Section: Introductionmentioning
confidence: 99%